Lifestyle Assessment and Motivations of Vegan Population in Chandigarh Tricity: Insights from a Comprehensive Survey - , Muskan Ghai, Preeti Shukla, Rekha Kaushik, Suresh Bhise, Rashmi Kumari (Archives of Current Research International, 2025)
This study examines the status of veganism in the Chandigarh Tricity area through a comprehensive analysis of survey data and supporting literature. The findings reveal a growing awareness and interest in veganism among residents, with a majority demonstrating familiarity with its principles. Motivations for adopting a vegan lifestyle vary, encompassing health, ethical, and familial influences. While familial acceptance significantly impacts individuals' ability to maintain a vegan lifestyle, challenges such as limited food options in local stores exist. The study underscores the importance of community support networks and educational initiatives to promote veganism and sustainability in the region. Efforts to increase the availability of vegan-friendly options and foster a supportive social environment can facilitate the transition to and maintenance of a vegan lifestyle in Chandigarh Tricity.